Specifics of training clinical psychologists in modern conditions - Zubatiuk Оксана; Pyliagina Галина (Psychosomatic Medicine and General Practice, 2024)
Abstract. The article deals with the issues of quality training of professionals in the field of mental healthcare, namely clinical psychologists. This is an urgent problem in the context of the war in Ukraine. Postgraduate medical education is an important stage of their training and is included in the ongoing professional development of such specialists as a process of acquiring new knowledge and continuous improvement of professional skills. A master’s degree in Clinical Psychology is one of the most important types of quality training for mental health professionals. Such an educational and professional master’s program was developed by the academic staff of the Department of Psychiatry, Psychotherapy and Medical Psychology of Shupyk National Healthcare University of Ukraine, taking into consideration the complex challenges of the current stage of postgraduate education development in Ukraine and the new standards of higher education introduced in our country. The aim of this programme is to train professionals capable of solving complex tasks and innovative problems in the field of mental healthcare, as well as preventive mental health, psychocorrection of mental health-related diseases which are characterized by uncertainty of conditions and requirements and may require research and/or innovation. Its main task is to develop key competencies in the field of mental healthcare. An important component of the programme is the list of mandatory competences (integral, general and professional) that future clinical psychologists should acquire during their master’s studies, and that will determine their ability to successfully carry out professional activities.